TINJAUAN KONSTITUSI PEMILIHAN KEPALA DAERAH YANG DILAKSANAKAN SECARA LANGSUNG OLEH DEWAN PERWAKILAN RAKYAT DAERAH - Samhudi, Gamalel Rifqi; Hibaturrakhim, M Rizal (Collegium Studiosum Journal, 2024)
The government system in Indonesia involves a large contribution from regional governments, which is known that the government structure at the provincial level is led by the Governor, district or city by the Regent or Mayor who is elected through the general election of regional heads. Initially, the people elected the regional heads directly, then the electoral system switched to indirect elections through the Regional People's Representative Council. However, with the passing of the aquo Law, the community is opposed because the representative election system is considered contrary to the constitution and Pancasila.The purpose of this study is to be able to know and analyze how the Constitution and Legislation regulate Regional Head Elections in Indonesia, and to find out whether the Regional Head Elections elected by the Regional People's Representative Council are contrary to the Constitution. This research uses Normative Juridical research, which is a type of legal research conducted by analyzing available literature. The research specification used is that this research is a complete analytical descriptive of the state of positive law in society. This research uses Library Reasearch technique. The word “democratically elected” has a fairly broad meaning, so it includes direct elections by the people or indirect regional head elections conducted by the DPRD. Then the democratic system in Indonesia has a direct election system and an indirect election system, the indirect regional head election system is also a manifestation of the implementation of Pancasila democracy.